Economic and Feasibility Analysis of Bioenergy Production from Sawdust Via Hydrothermal Carbonisation for a Circular Economy - Diaz-Robles, L (Italian Association of Chemical Engineering - AIDIC, 2023)
Hydrothermal carbonisation offers a promising solution to transform organic waste from agricultural and forestry industries into a high-calorific hydrophobic solid fuel. While still in the early development stages, HTC shows potential for large-scale implementation. Computational simulations were conducted to assess the economic viability of an industrial-scale HTC process for sawdust of radiata pine, validated against experimental data for accuracy and reliability. Results indicate that mass yield depends on temperature, residence time, and biomass-to-water ratio (B/W), while the energy yield of the hydrochar was primarily influenced by the process time and temperature. Longer times and higher temperatures generally resulted in higher energy yields. This finding highlights the importance of optimising the process parameters to achieve the desired energy output. The economic analysis demonstrated the viability of the industrial-scale HTC process. The study considered a 20 y evaluation period with a discount rate of 8 % and a weighted average cost of capital (WACC) of 5.4 %. The Return on Equity (ROE) was found to be 17.4 %. Based on these findings, utilising radiata pine sawdust, with a residual biomass flow of 200 t/day, an operating temperature of 190°C, a reactor residence time of 1 h, a B/W ratio of 10 %, and a hydrochar pellet price of 300 CLP/kg (0.3 USD/kg) yields an economically viable scenario for stove pellet production. Sensitivity analysis showed that demand must not fall below 15 t/h for project feasibility, even when positive Net Present Value (NPV) conditions were met. © 2023, AIDIC Servizi S.r.l.